x²y"(x)-3xy'(x)+3y(x)=2(x^4)(e^x)(adsbygoogle = window.adsbygoogle || []).push({});

=>y"(x)-(3/x)y'(x)+(3/x²)y(x)=2x²e^x

i dont know how to approach this problem because the coefficients are not constant and i am used to being given y1 and y2

HELP!!!

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Solve by using variation of parameters

**Physics Forums | Science Articles, Homework Help, Discussion**